Placement of Suspects or Accused of Deviant Sexual Orientation in Indonesia - Lestari, Saskia Dinda (Audito Comparative Law Journal (ACLJ), 2025)
Based on Government Regulation Number 27 of 1983 concerning the Implementation of the Code of Criminal Procedure Article 19 Paragraph (2), Regulation of the Minister of Justice Number: M.04-UM.01.06 of 1983 concerning Procedures for Placement, Treatment of Prisoners and Procedures for State Detention Centers Article 1 Paragraph (2), Government Regulation Number 58 of 1999 concerning Terms and Procedures for the Implementation of Authorities, Duties, and Responsibilities for the Care of Prisoners Article 7 states that the placement of prisoners is classified as one of them is based on sex. Ayluna Putri better known as Lucinta Luna was secured by officers of the West Jakarta Police Drug Investigation Unit, The police decided to place Lucinta Luna in a women's prison because the court decree granted Lucinta Luna's sex change request and for security and tranquillity reasons, including preventing Lucinta Luna from being bullied according to this, this study aims to determine the arrangement for the placement of suspects or defendants of orientation deviations sexual. The type of research used is the normative legal research method. This study found that the regulations regarding the classification of detention areas separated by sex this regulation does not adequately respond to current social developments, because sexual orientation deviation is not solely based on sex, but there are social factors behind it so the government needs to make government regulations related to the detention of criminal offenders who experience abnormalities or deflections of sexual orientation.